Flexible mica films coated by magnetron sputtered insulating layers for high‐temperature capacitive energy storage - Chao Yin; Tiandong Zhang; Changhai Zhang; Yue Zhang; Chang Kyu Jeong; Geon‐Tae Hwang; Qingguo Chi (SusMat)
Abstract High‐temperature energy storage performance of dielectric capacitors is crucial for the next generation of power electronic devices. However, conduction losses rise sharply at elevated temperature, limiting the application of energy storage capacitors. Here, the mica films magnetron sputtered by different insulating layers are specifically investigated, which exhibit the excellent high‐temperature energy storage performance. The experimental results revealed that the PbZrO3/Al2O3/PbZrO3 (PZO/AO/PZO) interface insulating layers can effectively reduce the high‐temperature leakage current and conduction loss of the composite films. Consequently, the ultrahigh energy storage density (Wrec) and charge‒discharge efficiency (η) can be achieved simultaneously in the flexible mica‐based composite films. Especially, PZO/AO/PZO/mica/PZO/AO/PZO (PAPMPAP) films possess excellent Wrec of 27.5 J/cm3 and η of 87.8% at 200°C, which are significantly better than currently reported high‐temperature capacitive energy storage dielectric materials. Together with outstanding power density and electrical cycling stability, the flexible films in this work have great application potential in high‐temperature energy storage capacitors. Moreover, the magnetron sputtering technology can deposit large‐area nanoscale insulating layers on the surface of capacitor films, which can provide technical support for the industrial production of capacitors.